Design of capacitance to voltage converter for capacitive sensor transducer - Alam, A. H. M. Zahirul; Che Mustapha, Nurul Arfah; Khan, Sheroz; Islam, Md. Rafiqul (Science Publications, 2010)
Abstract: Problem statement: The design of Capacitance to Voltage Converter (CVC) for capacitive sensor transducer was presented. The proposed design will reduce the size, power consumption and supply voltage of the circuit and can be used in high frequency band transducer. Approach: The design was implemented using the Operational amplifier (Op amp) and capacitive network. The circuit was simulated using the PSPICE model parameters based on standard 0.13 μm CMOS process. Results: The design was able to measure a wide range of capacitance variations for the capacitive transducer. The performance analysis of the design showed desirable performance parameters in terms of response, low power consumption and a linear output voltage within the wide range of capacitive transducer capacitance variation for the power supply voltage of 1.2 V was achieved. Conclusion/Recommendations: The output voltage of the circuit varied linearly with the variation of capacitive transducer capacitance variation. The improved converter was compact and robust for integration into capacitive measuring systems and suitable for use in environment that making use of higher frequency band.